Book Reviews - Michele Campopiano; Enrico Pasini (Journal of Interdisciplinary History of Ideas)
Reviews of Lacaita and Martinelli (eds.), The Civilization of Modernity: An Anthology of Carlo Cattaneo’s Writings, Brill 2024; Gianfrancesco and Tarrant (eds.), The Science of Naples: Making Knowledge in Italy’s Pre-Eminent City, 1500–1800, UCL Press 2024; Maddaluno, Science and political economy in Enlightenment Milan, 1760–1805, Liverpool UP 2024.